Legal liability for violation of the legislation on the Responsible Treatment of animals - Zhusipova, Б.А.; Sopyhanova, А.Б.; Ybyray, Н.Ө. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
The article deals with topical issues related to bringing to justice for animal cruelty in modern Kazakh law. In this regard, there is a need to study offenses against animals, in particular violations of legislation on responsible treatment of animals. The purpose of the study is to study the legal regime of communication with animals in the modern legal system of the Republic of Kazakhstan, to determine the types of liability for violation of legislation on responsible treatment of animals, legal control over the protection of animals from erroneous manifestations, to prepare proposals to improve the rules and current legislation to ensure the needs of animals. The objectives of the study are to characterize the types of offenses based on foreign legislation and judicial practice, the reasoning of scientists and to give their own author's conclusions on improving the current legislation. The authors, starting with the analysis of the legal status of animals and ending with the attitude towards animals not only as things, but also recognizing them as beings capable of experiencing suffering and emotions, draw attention to the need to clarify the responsibility of the animal owner in this area of public relations in case of violation of the rules of keeping pets, a possible threat to the safety of others. Various branches of the law of the Republic of Kazakhstan analyzed the responsibility for animal cruelty established by civil, criminal and administrative law. The work carried out as a result allowed the authors to formulate a number of recommendations on current legislation in the field of regulating the situation when pets violate the rules of handling them.